Effect of Adverse Environment on Buckling of Composite Laminates - M. R. M., Rejab; M. M., Noor; R., Daud; K., Kadirgama; M. S. M., Sani (2009)
This paper examine how the critical load of Glass Fibre Reinforce Plastic (GFRP) changed if exposed to the ordinary water. The exposure duration is for four (4) week. Buckling test is the type of experiment had been done for this project. The experiment analyzes for two (2) types of boundary condition; both ends fixed and ends pinned. The reinforcement had been used are woven and chopped strand mat (CSM) types. The specimens were prepared by hand lay-up technique. ASTM D 3039-76 for tensile test was used to obtain the properties of specimen such as strength (σ), strain (ε), poison ratio (v) and Modulus Young (E). The actual volume fraction (Vf) of the composite comply the ASTM D2584-02 for burn-out test. The results from the buckling test method will compared the results from theory. After immersed the specimens in water, buckling critical load for CSM laminate is higher than woven type laminates and the composite experienced significant reduction of the strength. From results also, the long period of specimen exposed in the water will reduce the strength and decrease the critical point for buckling as well.